2020
DOI: 10.7759/cureus.11627
|View full text |Cite
|
Sign up to set email alerts
|

Non-Arteritic Anterior Ischemic Optic Neuropathy (NAION) Following a Hypovolemic Episode of Gastric Bleeding

Abstract: Non-arteritic anterior ischemic optic neuropathy (NAION) is a rare complication following acute bleeding. Patients present with varying vision loss and visual field defects. NAION is more commonly developed in patients with systemic disorders that may affect normal blood flow such as hypertension and diabetes. In this case, we report a 54-year-old man who complained of vision blurring following an episode of acute gastric bleeding. This report aims to review the pathology of this condition and present the find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…Measuring IOP and systemic blood pressure in patients with unilateral NA-AION, Yang et al found that there was a significant increase in IOP and decrease in OPP after changing position from a supine to lateral decubitus position at the affected eye site, suggesting that the posture-induced IOP may be a risk factor for NA-AION development [51]. Supporting this hypothesis, it should be noted that several cases of NA-AION manifest upon awakening [52]; therefore, a link with sleeping body posture could be plausible; -Acute arterial hypotension and acute hypovolemic episodes: NA-AION is described as a rare complication of acute bleeding, shock events, and hemodialysis [53,54]. An acute systemic hypotension that causes an abrupt reduction in the OPP beyond the crit-ical range of autoregulation mechanisms, or, in the absence of efficient autoregulatory mechanisms [18], may induce a significant ONH blood supply reduction [23]; -Nocturnal systemic arterial hypotension: considering that the acute vision loss at NA-AION presentation is noticed upon awakening in more than 70% of cases [52], it is suggested that nocturnal hypotension could be a precipitating risk factor for NA-AION, especially in so-called "deeper" subjects, i.e., subjects in which the physiological nocturnal hypotension occurring during sleep, due to the attenuation of the sympathetic tone, is significantly higher than in normal subjects; or in patients assuming anti-hypertensive medications at night.…”
Section: Risk Factors and Associated Comorbiditiesmentioning
confidence: 92%
See 2 more Smart Citations
“…Measuring IOP and systemic blood pressure in patients with unilateral NA-AION, Yang et al found that there was a significant increase in IOP and decrease in OPP after changing position from a supine to lateral decubitus position at the affected eye site, suggesting that the posture-induced IOP may be a risk factor for NA-AION development [51]. Supporting this hypothesis, it should be noted that several cases of NA-AION manifest upon awakening [52]; therefore, a link with sleeping body posture could be plausible; -Acute arterial hypotension and acute hypovolemic episodes: NA-AION is described as a rare complication of acute bleeding, shock events, and hemodialysis [53,54]. An acute systemic hypotension that causes an abrupt reduction in the OPP beyond the crit-ical range of autoregulation mechanisms, or, in the absence of efficient autoregulatory mechanisms [18], may induce a significant ONH blood supply reduction [23]; -Nocturnal systemic arterial hypotension: considering that the acute vision loss at NA-AION presentation is noticed upon awakening in more than 70% of cases [52], it is suggested that nocturnal hypotension could be a precipitating risk factor for NA-AION, especially in so-called "deeper" subjects, i.e., subjects in which the physiological nocturnal hypotension occurring during sleep, due to the attenuation of the sympathetic tone, is significantly higher than in normal subjects; or in patients assuming anti-hypertensive medications at night.…”
Section: Risk Factors and Associated Comorbiditiesmentioning
confidence: 92%
“…Fellow-eye involvement can be contemporary or sequential. The bilateral simultaneous form is rare and typically associated with acute severe systemic hypotension, extraocular surgery, or drugs assumption [53,65,80,83]. The sequential involvement of the fellow eye has been reported to occur in 15-30% of cases within five years of the first eye damage, with a median time between first and second eye involvement of 7-12 months [99].…”
Section: Clinical Signs and Symptomsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonarteritic anterior ischemic optic neuropathy (NAAION), the most common form of ischemic optic neuropathy, is characterized by sudden painless loss of vision and visual field (VF) defects accompanied by optic disk edema, which leads to optic atrophy in several months [ [1] , [2] , [3] ]. In the USA, NAAION affects between 2.3 and 10.3 people over 100,000 individuals per year and may occur at any age; yet, it is particularly common in patients >50 years old [ 4 ].…”
Section: Introductionmentioning
confidence: 99%